THE HISTORICAL- CRITIC METHOD AND ITS INFLUENCE IN CRITICAL CONDUCT OF STUDENTS IN THE HISTORY AND GEOGRAPHY SPECIALTY OF THE ISP “ARÍSTIDES MERINO MERINO” IN CAJAMARCA - Escalante Abanto, Casimiro (2014)
The objective of the present study is to determine the influence of the Historical-Criticism method in the critical conduct of students in the History and Geography specialty of the Superior Pedagogical Institute “Arístides Merino Merino”, in the province of Celendín, department of Cajamarca. In the investigation the Historical-Critic method was applied during a period of three months in subjects related to the specialty of History and Geography (academic year 2002-II) with the support of the author of the method (Dr Manuel Silva Rabanal) and the professors of the specialty. The aforementioned method was applied to a sample of 44 students with the objective of increasing in a significant way their critical conduct. The method consisted in the evaluation of entrance, permanent motivation, acquisition and generalization (observation, location, explanation, understanding, analysis, synthesis, comparison and experimentation), the critic (discrimination, sustentation, alternatives of solution and decision process), final evaluation and feedback. The results obtained from the use of a nonparametric statistical technique (T of Wilcoxon) and the Correlational Coefficient of Pearson, in an almost experimental work with the design of chronological series with Invest. Educ. 11 (19), 2007 91 EL MÉTODO HISTÓRICO-CRÍTICO a group, was managed to validate the alternating hypothesis, in the sense that this method significantly increased the critical conduct of students of the specialty of History and Geography in this institute.